The correlation between termination and compensation claim in contractual liability - Awat Omar Qadir Haji (The Scientific Journal of Cihan University– Sulaimaniya, 2020)
It is important to give creditor more than one chose in binding contracts for both sides. The creditor must be able to ask compensation and enforcement of the contract as the same time, but according to Iraqi court of cassation and the court of cassation in Kurdistan the creditor couldn’t able to asked compensation and implementation of the contract as the same time when the contract has been broken by the debtor, or the debtor breaches its obligations , so his judicial direction makes a problem .The research discusses this problem and the relationship between compensation and termination of contract according to Iraqi civil law and Iraqi jurisdiction. The research criticizes Iraqi judicial direction about it, moreover it finds its solution to solve the problem.